Teknologi Informasi Keruangan: Pengalaman Penerapan di Lingkungan Pemerintahan Kota di Indonesia - Agus Prijadi Saido (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Geographic information technology is increasingly adopted and implemented in somegovernmental city in Indonesia. A success story and stagnancy of its implementation anddevelopment in LIS Semarang and Surakarta City, An IT-based Transparant Planning andMonitoring of City Planning Systems in Denpansar City, and an effort to raise thePerformance of City Fire Deparment in Padang City were studied and elaborated to providea better understanding, a more complete, firm and solid knowledge as well as good and bestpractices in developing and implementing geographical related information technology.Geographycal information systems as one main component of geomatics or geographicinformation technology is one of the most promising technology for the Autonomus CityGovernment in adapting the e-Government if and only if the city is very well aware andprepare for fostering and stregthening the city capacity building.Keywords: ICT, geomatics, autonomus city government, e-government.